Socialist reconstruction : a better future for the United States. (Liberation Media, 2022)
A vision of the first decade of socialism in the United States. The diverse multinational working class has achieved political supremacy and is actively eliminating bigotry, racism, and national oppression as it expands economic, social, and political democracy.